Key data on teaching languages at school in Europe. 2012 Edition (Luxembourg, 2012)
"As in the two previous editions, this issue of the Key Data series will provide for an exhaustive picture on how languages are taught at schools from the point of view of teaching organisation, pupils' participation and teachers training. For the first time, this edition will be using results from SurveyLang, a European Survey on Language Competences. This joint publication with Eurostat will provide for a comparative analysis based on different sources, combining statistical, descriptive and empirical indicators."